The China–India–Pakistan Nuclear Trilemma and Accidental War - Prakash Menon (Journal for Peace and Nuclear Disarmament, 2022)
The perspective of the paper is the geopolitical contestation between China–India–Pakistan, which frames the contours of the nuclear trilemma that is nested in the broader global nuclear weapons framework. Territorial disputes harbor the potential for conflict under the nuclear overhang between China–India and India–Pakistan. The two dyads are structurally separate but are also connected. Beliefs systems that shape nuclear doctrine have commonality in the China–India dyad. But such is not the case in the India-Pakistan dyad. There is, however, political recognition of the dangers that inhabit the unexplored space of conventional war under the nuclear over hang. The greater danger of nuclear war in both dyads is concealed in the inability to control escalation of conflicts that may have small beginnings but can potentially spin out of control. The paper uses Clausewitz escalation model to highlight this crucial issue. The policy prescriptions are therefore directed on never testing the boundaries of the nuclear threshold and relate to reduction of alert levels. A Global No First Use Treaty is proposed and one that is possible only if the dangers of nuclear war are publicized at the global level thus forcing the hand of political leaders. This is an imperative step to free the leadership from the shackles of varied impractical nuclear strategies that are unable to answer the question – what happens after the first nuclear weapon is fired.